Measurement of iron stores in cirrhosis using diethylenetriamine penta-acetic acid. Issue 11 (November 1970) - Barry, Michael; Cartei, Guiseppe; Sherlock, Sheila
Abstract : The chelating agent diethylenetriamine penta-acetic acid was used to measure iron stores in 83 patients with chronic liver disease. Iron chelation was normal in patients with chronic cholestasis. Chelation was increased above the control range in 14 out of 26 patients with alcoholic cirrhosis, in nine out of 28 patients with non-alcoholic cirrhosis, and in 11 out of 15 cirrhotics with a portacaval anastomosis. Iron stores in excess of 1·5 g were predicted from the results in 24 subjects; however, in only three were the values in the range found in propositi with untreated idiopathic haemochromatosis. Increased chelation did not correlate with hepatocellular impairment per se but was associated in 18 cases with surgical or large spontaneous portal systemic shunts. Exogenous factors for excess iron were present in three cases with alcoholic cirrhosis and portal systemic collaterals in one, but no special factor apart from alcoholism was apparent in the remainder. The correlation between chelatable iron and stainable liver iron content was not close and was better in haemochromatosis than in other forms of cirrhosis; in some cases considerable siderosis was present with normal or only slightly increased chelation values.